Assistance with the Financial and Budget Reports of the East Tanjung Jabung Regency's Food Security Service for the Fiscal Year 2024 - Antoni, Amat; Abidin, Zaenal; Wandi, Wandi; Fatimah, Siti (Zabags International Journal of Engagement, 2024)
This research aims to analyze the effectiveness of the assistance program in improving the quality of financial reports of the East Tanjung Jabung Regency Food Security Office, identify the main obstacles in preparing accountable reports, and determine the most effective methods to enhance Human Resource capacity in budget management. The methodology used is a qualitative approach with a case study method, involving in-depth interviews, observations, and document analysis. The research results show that the assistance program successfully improved compliance with accounting standards and report accuracy, although obstacles such as limited human resources, technology, and regulatory understanding remain significant. In conclusion, continuous practice-based training methods, intensive mentoring, and the use of technology are the most effective ways to enhance Human Resource capacity. The recommendation given is the need for continuous training, modernization of technology, and the establishment of a work culture that supports accountability and transparency in the preparation of financial reports